A novel method for decaying DC component removal with regard to frequency fluctuations. Issue 1 (4th January 2016) - Tajdinian, Mohsen; Montaser Kouhsari, Shahram; Mohseni, Kazem; Zareian Jahromi, Mehdi
Abstract : Purpose: – Decaying DC component has important effect on extracting the fundamental component phasor. It directly affects the precision of protective relaying algorithms which act based on fundamental frequency component. It can be noted that decaying DC component, harmonic components and off-nominal frequency conditions are the major issues which strongly effect phasor estimation. The paper aims to discuss these issues. Design/methodology/approach: – This paper proposes a novel hybrid approach for fundamental phasor estimation in order to remove the decaying DC component using Hilbert Transform and Discrete Fourier Transform. Findings: – The proposed method (PM) converges to the original value in one cycle in presence of harmonic components and off-nominal frequency condition. In addition, proposed algorithm is able to detect the frequency fluctuation. Thus, it is applicable for static and dynamic conditions. An extensive set of simulation results across static and dynamic validations demonstrated that the proposed approach has faster convergence and better precision than the present methods. In addition, during harmonic distortion and also frequency fluctuation, the PM provides a correct and reliable response. Originality/value: – The PM can calculate the DC component exactly from fault current signals and can be used in digital protection algorithms for phasor estimation.